Peningkatan Keamanan Aplikasi Web Menggunakan Web Application Firewall (WAF) Pada Sistem Informasi Manajemen Kampus Terintegrasi - Randi Rizal; Yusuf Sumaryana (STMIK IKMI Cirebon, 2021)
Increasing the security of web applications on the integrated campus management information system needs to be done because the application is accessed by public networks so that there are many attacks and attempts to prevent threats from attackers. This study applies a Web Application Firewall (WAF)-based application security using ModeSecurity and Core Rules Set from Owasp which aims to improve the security system of the web application by using a firewall. This study uses an experimental method by implementing a Web Application Firewall (WAF) as a web-based protection system, then the process of analysis and testing to obtain accurate advice on firewall implementation. The results of this study indicate that the firewall used with Web Application Firewall (WAF)-based ModeSecurity has succeeded in stopping attacks from attackers using Cross Site Scripting (XSS) and SQL Injection methods.